125I seed brachytherapy with cement augmentation versus cement alone for acetabular metastases: a comparative study - Sun, Zhi-qian; Li, Shuai; Zhu, Bao-quan; Sun, Qi-yu; Li, Min (Frontiers in Oncology, 2025)
ObjectiveAs the survival of cancer patients improves, the incidence of bone metastases increases. Acetabular metastases often cause severe pain, limit hip mobility, and impair quality of life. Percutaneous cement augmentation (PCA) provides short-term pain relief and improves mechanical stability, but its anti-tumor effect is limited. 125I seed brachytherapy offers precise local tumor control but cannot enhance bone strength. We proposed a novel strategy combining 125I seeds with cement augmentation to achieve better tumor killing and bone stabilization.MethodsWe retrospectively analyzed 64 patients (determined by power analysis assuming α=0.05, β=0.2, and expected difference in VAS scores of 1.5) with acetabular metastases who underwent either PCA alone (group A, n=34) or 125I seed brachytherapy plus PCA (group B, n=30) between December 2008 and December 2022. Pain intensity (VAS), functional status (ECOG), and complications were evaluated as primary endpoints before and up to 6 months after treatment. Survival analysis was performed using Kaplan-Meier method with log-rank test.ResultsThe two groups had similar baseline characteristics. Group B showed significantly lower mean VAS scores (mean difference: 2.1; 95% CI: 1.6-2.6; p < 0.001) and ECOG scores (mean difference: 1.51; 95% CI: 1.1-1.9; p < 0.001) at 6 months post-treatment compared to group A. Complication rates were comparable between groups (5.9% vs 3.0%, p = 0.62), with no significant difference in median survival (16.8 vs 16.7 months, p = 0.85).ConclusionCombined ¹²5I seed brachytherapy and PCA (¹²5I-PCA) provides superior long-term pain control and functional outcomes compared to PCA alone for acetabular metastases. This is attributed to the synergistic effect of PMMA-mediated mechanical stabilization and continuous low-dose radiation-induced tumor suppression, effectively addressing the transient cytoreduction limitation of standalone PCA. Integration of TPS(Treatment Planning System)-guided brachytherapy dosing with precise CT-guided cementoplasty represents an effective and safe palliative strategy for these complex lesions.